Legal Disruption and Sharia Arbitration: Navigating Change, Measuring Impact, and Fostering Innovation - Hossein, Zainal Arifin; Mahmudulhassan, M (Indonesian Journal of Islamic Economic Law, 2024)
This article evaluates the doctrinal challenges encountered by the law amid technological advancements, specifically in the areas of blockchain technology, smart contracts, digital assets, and data privacy. Certain conventional legal doctrines, including intellectual property law, privacy, and evidence, and the principle of nonrefoulement, may no longer be applicable amidst the introduction of disruptive technological developments. We present methods for identifying irrelevant legal issues using the TRIZ approach, which enables the identification, evaluation, and updating of legal doctrine. Additionally, this article illustrates how TRIZ principles can develop more adaptable contract principles in response to technologies such as smart contracts. By applying these principles, the law can more effectively manage change, promote innovation in consumer protection, and support the use of smart contracts.